APLIKASI SIG UNTUK PENENTUAN HIRARKI KLASIFIKASI FUNGSI JALAN DALAM PENGEMBANGAN PARIWISATA REMBANG - M, M. Nurul Huda (Geo-Image, 2013)
The improvement of road network using tools of Geographic Information Systems (GIS) can play a role in regional development, especially on the tourism potential. This study aims to examine how the hierarchy of road classification system based on GIS-based functions and how it influences the level of service roads to the development potential of tourism in the district of Apex. Study sites are located in the District of Apex with the object of research in the segment - which includes roads primary roads, secondary roads and local streets and sights. The results showed that the hierarchical classification of roads in the district of Apex function is divided into three sections: the main highway / arterial primary, secondary road / primary collector, local road or street between the environments. The low value of the LOS path the higher the level of service, which means the higher the development of its tourism potential to be developed as shown in the tourist district Lodan Embung nest with a value of 0.12 LOS belonging to the characteristic level of service A